2019
DOI: 10.1016/j.celrep.2019.05.101
|View full text |Cite
|
Sign up to set email alerts
|

Early Seizure Activity Accelerates Depletion of Hippocampal Neural Stem Cells and Impairs Spatial Discrimination in an Alzheimer’s Disease Model

Abstract: SUMMARY Adult hippocampal neurogenesis has been reported to be decreased, increased, or not changed in Alzheimer’s disease (AD) patients and related transgenic mouse models. These disparate findings may relate to differences in disease stage, or the presence of seizures, which are associated with AD and can stimulate neurogenesis. In this study, we investigate a transgenic mouse model of AD that exhibits seizures similarly to AD patients and find that neurogenesis is increased in early stages of disease, as sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 107 publications
3
57
0
1
Order By: Relevance
“…The activation of adult NSCs transiently increases the number of new neurons but ultimately leads to the depletion of NSCs, indicating that the supply of new neurons is limited [69,70]. This mechanism has also been proposed in epilepsy models [71]. In epileptic seizures, abnormal firing stimulates NSCs, temporarily increasing the division of NSCs and promoting neurogenesis.…”
Section: Challenges Of Regenerative Therapy Involving the Activation mentioning
confidence: 93%
“…The activation of adult NSCs transiently increases the number of new neurons but ultimately leads to the depletion of NSCs, indicating that the supply of new neurons is limited [69,70]. This mechanism has also been proposed in epilepsy models [71]. In epileptic seizures, abnormal firing stimulates NSCs, temporarily increasing the division of NSCs and promoting neurogenesis.…”
Section: Challenges Of Regenerative Therapy Involving the Activation mentioning
confidence: 93%
“…Early-onset epileptic activity in 1-and 2-month-old hAPP-J20 mice. Reproduced with permission from (Fu et al 2019).…”
Section: Fig2 Early-onset Neuronal Network Hyperexcitability In Hapmentioning
confidence: 99%
“…FosB can recruit histone-modifying proteins to target genes, a process that has been well-characterized in the nucleus accumbens (NAc), in which FosB accumulates after chronic exposure to drugs of abuse and regulates gene expression (Renthal et al, 2008;Robison and Nestler, 2011;Nestler and Luscher, 2019). Our work demonstrated that seizures induce FosB accumulation in the hippocampus of two mouse models with spontaneous recurrent seizures: pilocarpine-treated mice (Pilo mice) as well as transgenic mice that express human amyloid precursor protein (APP) carrying mutations linked to AD (line J20) (Corbett et al, 2017;You et al, 2017;Fu et al, 2019). Importantly, we showed that FosB also accumulates in the hippocampus of patients with AD and in patients with temporal lobe epilepsy (TLE) (You et al, 2017).…”
Section: Introductionmentioning
confidence: 79%